Carbohydrate-based approach for the total synthesis of 1,3-polyol/alpha-pyrone antifungal natural products - Ramana, Chepuri V.; Srinivas, B.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Organic Chemistry, 2005)
An elimination and stereoselective hydrogenation of alpha-D-glucoheptonic-gamma-lactone derivative has been applied to prepare a differentially protected anti,anti-1,3,5-triol system, the utility of which has been extended for the total synthesis of anti-fungal 1,3-polyol/alpha-pyrone natural products.